Clinical features, pathophysiological mechanisms, and multidisciplinary management strategies for rhinitis-induced adenoid facies in children and adolescents: a review - Ding, Ying; Xu, Yan; Han, Shanshan; Gao, Min; Wang, Long; Xu, Shanshan; Guo, Ting; Bai, Huiwen (Frontiers in Allergy, 2025)
Chronic rhinitis and its associated persistent nasal obstruction and mouth breathing are core factors leading to the development of characteristic “rhinitis face” or “adenoid facies” in children and adolescents. This review elucidates the diverse clinical manifestations of “rhinitis face,” including: persistent open-mouth posture; abnormal patterns of facial skeletal growth, such as midface hypoplasia and increased lower anterior facial height resulting in “long face syndrome”; alterations in jaw morphology and position, including maxillary constriction, high-arched palate, and mandibular retrognathia or posterior-inferior rotation; and various dentoalveolar malocclusions, such as proclined maxillary incisors, lip incompetence, narrow dental arches, and open bite. Additionally, these include characteristic periorbital skin changes, such as “allergic shiners” (dark circles under the eyes due to venous stasis or pigmentation), Dennie-Morgan lines (infraorbital folds associated with atopy), and, in some patients, eyelash trichomegaly (increased eyelash growth) potentially due to chronic inflammation. The nose may also exhibit a transverse nasal crease (the “allergic salute” sign) from repetitive rubbing. This paper delves into its pathophysiological mechanisms, emphasizing that mouth breathing patterns triggered by chronic nasal airway obstruction are the initiating factor. This alters the equilibrium of orofacial muscle forces, interferes with normal tongue posture and function, and affects the normal growth trajectory of the maxillofacial skeleton. Combined with local inflammatory responses and mechanical stimuli, these factors collectively contribute to the development of these complex facial characteristics. Clinical assessment requires a comprehensive approach including medical history, detailed physical examination, and various ancillary investigations such as nasal endoscopy, imaging studies (x-ray, CT, CBCT), cephalometric analysis, nasal patency tests, and allergen testing. “Rhinitis face” not only affects aesthetics but can also lead to severe maxillofacial skeletal deformities, dental malocclusions, temporomandibular joint dysfunction, and sleep-disordered breathing. It can also profoundly impact respiratory physiology, exercise tolerance, speech clarity, psychological well-being, and quality of life. Its long-term effects can persist into adulthood, although skeletal adaptive changes diminish after growth cessation. Regarding gender differences in its prevalence, existing data suggest that upstream factors (such as obstructive sleep apnea) may have a higher prevalence in males, and the impact of mouth breathing on facial morphology might exhibit sex-specific differences. However, the overall sex ratio for “rhinitis face” remains inconclusive. Concerning the notion that rhinitis causes enlarged eyes, there is currently no scientific evidence to support an actual increase in eyeball size. The perception of “larger eyes” is more likely a visual contrast effect due to allergic shiners, Dennie-Morgan lines, and possible mild eyelid edema. Regarding public opinions about finding “rhinitis face in girls” attractive, this review emphasizes the lack of scientific basis for such views, which are more likely subjective perceptions or cultural phenomena. Medically, “rhinitis face” is considered a pathological condition requiring active intervention. Management strategies for affected children emphasize a multidisciplinary approach, including early diagnosis and active treatment of the primary nasal pathology (e.g., allergic rhinitis, adenoidal hypertrophy), correction of improper mouth breathing habits through methods like orofacial myofunctional therapy, and, when necessary, intervention by orthodontists or maxillofacial surgeons (e.g., rapid maxillary expansion, fixed orthodontic treatment). This review aims to provide clinicians with a comprehensive understanding of “rhinitis face” to facilitate its early recognition, standardized diagnosis and treatment, and comprehensive management.